Research of Acoustic Responses of Biological Objects for Detection of Malignancies - Mkrtchyan, A. H.; Nalbandyan, V. V.; Hakobyan, A. S.; Hovhannisyan, H. T.; Avetisyan, K. V.; Harutyunyan, V. S.; Papazyan, A. A.; Shadyan, E. S.
The technique of diagnosing of malignancies, in particular sarcomas like S-180, in biological objects (mice) utilizing the new contactless method of diagnostics developed on the basis of modulation acoustic spectroscopy which is carried out by scanning of objects by acoustic field formed by package of the modulated electromagnetic waves of different frequency is offered. Comparative analysis of the amplitude-frequency distributions of acoustic responses of the studied healthy and sick objects received as result of scanning gives the chance of detection and determination of prevalence of malignancies.
Keywords: Physics; Cross-Disciplinary